Methods of calculating the exhaust hoods - Rybak-Wilusz, Elżbieta; Kut, Paweł (Instal, 2020)
Contaminants generated in technological processes cause a decrease in air quality in the internal environment. The content of harmful substances in workplaces should not exceed the maximum permissible concentrations. The local exhaust ventilation systems used in workplaces serve to reduce the content of contaminants and maintain the appropriate air quality. The key element of the local exhaust ventilation system is the canopy hood. It is located in the zone of formation of harmful substances, captures the contaminants removed together with the extracted air stream. The paper presents methods of calculating the exhaust hoods. The principles of hood dimensioning and the main factors determining the methodology of calculating the amount of extracted air were determined. It was indicated that the application of an appropriate method of calculating mainly depends on the type of source emitting the pollution, the location of the hood in relation to the source of contaminant and the nature of movement of the air stream extracted through the hood.